2022
DOI: 10.2337/db22-218-or
|View full text |Cite
|
Sign up to set email alerts
|

218-OR: The Effect of Insulin Degludec vs. Insulin Glargine U100 on Continuous Glucose Monitoring (CGM) Recorded Glycemic Metrics in People with Type 1 Diabetes and Recurrent Nocturnal Severe Hypoglycemia

Abstract: Background and Aims: Insulin Degludec (IDeg) , in comparison with Insulin Glargine U100 (IGla) , reduces the risk of hypoglycemic events in people with type 1 diabetes (T1D) . The impact on CGM assessed glycemic metrics: the coefficient of variation (CV) , time in range (TIR) , time below range (TBR) , and time-above range (TAR) is less known. We present CGM results from the HypoDeg trial comparing treatment with IDeg and IGla in people with T1D and recurrent nocturnal severe hypoglycemia. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Brøsen et al randomized 149 persons with T1D who had had ≥1 severe nocturnal hypoglycemia episode during the prior 2 years to insulin degludec versus insulin glargine U100, finding coefficient of variation of continuous glucose monitoring during the night significantly lower at 35.7% versus 39.6%, with significantly lower time below 54 mg/dl at 1.8% versus 3.1% 38 . Bergenstal et al reported a 12‐week open‐label trial of 343 T1D persons randomized to insulin glargine 300 U/ml and degludec 100 U/ml showing similar within‐day and between‐day glucose coefficient of variation, suggesting comparable clinical benefit of these two insulin preparations 39 …”
Section: Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Brøsen et al randomized 149 persons with T1D who had had ≥1 severe nocturnal hypoglycemia episode during the prior 2 years to insulin degludec versus insulin glargine U100, finding coefficient of variation of continuous glucose monitoring during the night significantly lower at 35.7% versus 39.6%, with significantly lower time below 54 mg/dl at 1.8% versus 3.1% 38 . Bergenstal et al reported a 12‐week open‐label trial of 343 T1D persons randomized to insulin glargine 300 U/ml and degludec 100 U/ml showing similar within‐day and between‐day glucose coefficient of variation, suggesting comparable clinical benefit of these two insulin preparations 39 …”
Section: Insulinmentioning
confidence: 99%
“…Brøsen et al randomized 149 persons with T1D who had had ≥1 severe nocturnal hypoglycemia episode during the prior 2 years to insulin degludec versus insulin glargine U100, finding coefficient of variation of continuous glucose monitoring during the night significantly lower at 35.7% versus 39.6%, with significantly lower time below 54 mg/dl at 1.8% versus 3.1%. 38 Bergenstal et al reported a 12‐week open‐label trial of 343 T1D persons randomized to insulin glargine 300 U/ml and degludec 100 U/ml showing similar within‐day and between‐day glucose coefficient of variation, suggesting comparable clinical benefit of these two insulin preparations. 39 Mathiesen et al 40 compared 1434 women with T1D during pregnancy receiving insulin aspart versus 406 receiving other bolus insulin preparations, showing significantly lower third trimester HbA1c of 6.59% versus 6.75%, but with similar propensity‐score matched likelihood of severe hypoglycemia, abortion, preterm delivery, preeclampsia, birthweight large for gestational age, and major congenital malformations.…”
Section: Insulinmentioning
confidence: 99%